Bonsoir,
Développe et réduis:
k(a + b) = ka + kb
A = 5(2x - 7)
A = 10x - 35
B = -4(-3x + 1)
B = 12x - 4
C = 4 - 3(x - 5)
C = 4 - 3x + 15
C = -3x + 19
D = 5x - 5(-2x + 1)
D = 5x + 10x - 5
D = 15x - 5
E = 2(3x + 5) - 4(x + 2)
E = 6x + 10 - 4x - 8
E = 2x + 2
------------------------------------------------------------------
Développe et réduis:
(a + b)(c + d) = a*c + a*d + b*c + b*d
A = (x + 3)(x + 5)
A = x² + 5x + 3x + 15
A = x² + 8x + 15
B = (2x - 3)(-x + 2)
B = -2x² + 4x + 3x - 6
B = -2x² + 7x - 6
C = (-4x + 3)(2x + 1)
C = -8x² - 4x + 6x + 3
C = -8x² + 2x + 3
D = (7x - 2)(5x - 4)
D = 35x² - 28x - 10x + 8
D = 35x² - 38x + 8
E = (-3x - 4)(8x - 7)
E = -24x² + 21x - 32x + 28
E = -24x² - 11x + 28
------------------------------------------------------------------
Développer et réduire :
A = 5 + (2x - 7)(4 - 3x)
A = 5 + 8x - 6x² - 28 + 21x
A = -6x² + 29x - 23
B = 3 - (4x + 1)(-x + 2)
B = 3 - (-4x² + 8x - x + 2)
B = 3 - (-4x² + 7x + 2)
B = 3 + 4x² - 7x - 2
B = 4x² - 7x + 1
C = 5x - 1 + (2x - 3)(3x + 1)
C = 5x - 1 + 6x² + 2x - 9x - 3
C = 6x² -2x - 4
D = 4x² - (-5x + 2)(x - 3)
D = 4x² - (-5x² + 15x + 2x - 6)
D = 4x² - (-5x² + 17x - 6)
D = 4x² + 5x² - 17x + 6
D = 9x² - 17x + 6
E = (2x - 3)(x + 5) - 4(2x - 1)
E = 2x² + 10x - 3x - 15 - 4(2x - 1)
E = 2x² + 7x - 15 - 4(2x - 1)
E = 2x² + 7x - 15 - 8x + 4
E = 2x² - x - 11
Bonne soirée.